Financial Organisation and operations of the IMF (Washington, D. C. International Monetary Fund, 1991)
A pamphlet prepared by staff members of the treasurer's Department of the IMF whose daily work is its subject matter. The first edition was completed under the direction of Warren Coats. The work is essentially a collaborative effort , encompassing staff throughout the institution. The second pamphlet reflects policy and operational changes since June1991.
opc 23/12/16
Loans
Keywords: International Monetary Fund; Financial management